miR-15b-5p Promotes Growth and Metastasis in Breast Cancer by Targeting HPSE2 - Wu, Balu; Liu, Guohong; Jin, Yanxia; Yang, Tian; Zhang, Dongdong; Ding, Lu; Zhou, Fuling; Pan, Yunbao; Wei, Yongchang (Frontiers in Oncology, 2020)
Researchers have been interested in microRNAs (miRNAs) for a long time as they can participate in many biological behaviors of various tumors. Prior studies have reported that miR-15b-5p exhibits a dual effect in prompting or inhibiting tumor progression in different tumors. However, the role of miR-15b-5p in breast cancer (BC) and its functional mechanisms remain unclear. The main objective of this paper is to explore the role and mechanism of miR-15b-5p in BC. This study investigated the role of miR-15b-5p in breast cancer through in vitro and in vivo experiments. Results demonstrated that miR-15b-5p expression was significantly up‐regulated in BC comparison with normal samples and was positively correlated with poor overall survival in patients with BC. Knocking down miR-15b-5p restrained cell growth, invasiveness and induced apoptosis in MCF-7 and MD-MBA-231 cells, while these effects were reversed after overexpression of miR-15b-5p. Next, we revealed a negative correlation between HPSE2 and miR-15b-5p expression in BC tissues and demonstrated that HPSE2 as a direct target of miR-15b-5p via dual-luciferase assay. Knocking down miR-15b-5p significantly increased HPSE2 expression at mRNA and protein levels in BC cells. In addition, miR-15b-5p knockdown significantly inhibited tumorigenicity in BC xenograft model mice. In summary, this study showed that miR-15b-5p promotes breast cancer cells proliferation, migration, and invasion by directly targeting HPSE2 and may serve as a target for the diagnosis and therapy of breast cancer patients.